Series production technology for high-performance fibre composite components with structure integrated sensors - Kroll, Lothar; Gelbrich, Sandra; Elsner, Holg (Computer Assisted Methods in Engineering and Science, 2007)
The integration of electronic units, sensors and actuators into complex function-oriented systems is one of the key points in the development of intelligent fibre composites. A wide range of materials is available for that purpose, for example piezoelectric textile sensors, fibre-optic fibres as well as shape memory alloys and prefabricated information elements. These elements can be used to create active fibre composites ("smart composites") with selective properties, which are suitable especially for application in stressed lightweight components. While the functionality of these solutions could be proved on a laboratory scale, appropriate manufacturing strategies for a competitive series production of components in automotive and mechanical technologies have not been realised so far. One crucial obstacle which impedes a breakthrough for such active lightweight components is the lack of technologies suitable for large-scale production. Generally, these complex systems are manually integrated into the fibre composite with either prefabricated layer materials or as individual elements, or applied to the surface of the fibre composite compound, thus preventing process automation. Therefore, the goal of the Institute of Mechanical Engineering and Plastics Technology (Chemnitz University of Technology) is to develop application-oriented technological solutions for series production.